What is the decentered state?. (January 2022) - Bevir, Mark
This article provides an introduction to discussions and empirical studies of the decentered state. The first section traces the historical origins of the concept of the decentered state. Group theory and interorganizational theory drew attention to the role of diverse actors in policymaking. The study of policy networks explored these actors and their relationships. The concept of the hollow state arose to describe a state made up of proliferating networks. Finally, postfoundationalists amended these earlier ideas by insisting that the state should not be reified. There are, then, at least three different versions of the decentered state—the pluralist state, the hollow state, and the stateless state. The second section shows how the postfoundationalism of decentered theory transforms the earlier debates about network governance and pluralist democracy. The final section suggests that decentered theory privileges empirical studies of the stateless state and in particular of narratives, rationalities, and resistance.